The Effects of Firm Size and Leverage on Profitability: Empirical Evidence from Textile and Garment Manufacturing Companies Listed on the Indonesia Stock Exchange, 2020–2025 - Hizbul Khootimah Az Zaakiyyah; Nita Laila Asyifa; Putri Pramestiwi Kusumojati (PT. LITERASI SAINS NUSANTARA, 2026)
This study examines the effects of firm size and leverage on the profitability of textile and garment manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2025 period. A quantitative approach employing an explanatory research design was adopted using secondary data obtained from the companies' annual financial statements. The sample consisted of 76 firm-year observations selected through purposive sampling. Data were analyzed using descriptive statistics, classical assumption tests, and multiple linear regression analysis. The findings reveal that both firm size and leverage have positive and statistically significant effects on profitability, measured by Return on Assets (ROA). Furthermore, leverage demonstrates a stronger influence on profitability than firm size. These findings support the Resource-Based View and Trade-Off Theory, suggesting that effective resource utilization and optimal capital structure management contribute to improved corporate financial performance. The study provides practical implications for corporate managers in optimizing asset utilization and financing decisions to enhance profitability while offering valuable insights for investors in evaluating corporate financial performance and making investment decisions.